Martin, F., Demirdache, H. 2020. Partitive accomplishments across languages. Linguistics 58: 1195-1232. - Zhang, Zichen (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2023)
.